Analysis of the Function of Schottky Barrier Diode in Microwave Rectifying Circuit - Yong Xia; Xiaowei Shi (International Journal of Antennas and Propagation)
In this paper, a new viewpoint on the function of the Schottky barrier diode (SBD) in microwave rectifying circuit is proposed. In the analog circuit field, it has been formed a relatively mature theoretical system about the rectifying circuit, which constitutes the base of subsequent rectifier design schemes. The researchers take it for granted that the SBD selected as the core component in the microwave rectifying circuit should play the role of rectifying in the same way as the diode in the analog circuit. The fact that the one-directional conductivity of the SBD is not observed in microwave circuit by the means of simulation and experiment is proposed. The basis of the former rectification theory is in doubt here. Due to the interaction of the microstrip line and SBD, the DC component generated at the front end of SBD is the key reason for the DC output power of rectifying circuit. The way of DC generation is completely different from the previous idea. Accurate and in-depth understanding of the function of SBD in microwave rectifying circuit will help the researchers to make use of SBD rightly and design circuit in future applications.